E-Cigarettes: Biological Effects, Addiction Risk, and Public Health Challenges – A Narrative Review - Turlej, Kamil; Kowalczuk, Dmytro; Lazitskaya, Darya; Kasianik , Viktoryia; Sobchynskyi, Mykola; Milasheuskaya , Valeryia; Myrnyi, Andrii; Kiełbaszewska , Iga; Surosz , Natalia; Miraniuk , Katsiaryna (Quality in Sport, 2025)
E-cigarettes have gained popularity as an alternative to traditional cigarettes; however, a growing body of research highlights potential health risks associated with their use. Chemical analyses have revealed the presence of toxic organic compounds and heavy metals, the inhalation of which is linked to an increased risk of respiratory diseases, including cancer. This risk may exceed acceptable safety thresholds, particularly with prolonged exposure. Although e-cigarettes exhibit a lower addictive potential compared to traditional cigarettes, their use—especially among adolescents—has been associated with worsening asthma symptoms and a higher frequency of wheezing episodes. Adverse effects on the cardiovascular system have also been demonstrated, along with potential negative outcomes during pregnancy and for fetal development. A clear link has been established between e-cigarette use and EVALI (E-cigarette or Vaping product use-Associated Lung Injury), a severe lung condition related to vaping. While some evidence suggests that nicotine-containing e-cigarettes may aid in smoking cessation, the safety of their use for this purpose remains uncertain.